Measurement of Generic Skills of Students: A Systematic Literature Review - Siska Merrydian; Yetti Supriyati Saefudin; Anan Sutisna (Jurnal Penelitian Pendidikan IPA, 2023)
One of the talents that students must have to face rapidly developing global problems is generic skills. Therefore, it becomes important to measure generic skills in students. The method used in this study is a systematic literature review using the PRISMA diagram. The database used to search for literature utilized two digital libraries, namely Google Scholar and Scopus. In order to make the selected literature relevant, the search used the keyword "generic skills". Furthermore, screening was carried out to obtain scientific article publications from 2010 to 2023 that discuss generic skills. The results of the search for scientific articles contained thirty articles that would be analyzed and synthesized. The analysis technique used is the narrative method by grouping the extracted data. This study is expected to collect student generic skills measurement instruments.